Comparative evaluation of bone mineral density in premature birth and low birth weight children by fractal analysis on panoramic radiographs - Berrin Çelik; Esra Ceren Tuğutlu; Zeynep Betül Arslan (BMC Oral Health)
Abstract Background Bone mineral density (BMD) is a critical indicator of skeletal health, and its assessment is particularly important in children born premature or with low birth weight (LBW), as these conditions are associated with altered bone development. The aim of this study was to compare the BMD values of premature and LBW children with those of normal term and normal birth weight children via fractal dimension (FD) analysis of panoramic radiographs. Methods This study included a total of 60 panoramic radiography images of children aged 6–15 years. The study group consisted of children born premature (before 37 weeks) and with low birth weight (less than 2500 g). The control group consisted of children born at normal term with normal birth weights. In addition, body mass index (BMI), maternal age at birth, and frequency and duration of incubation were recorded. FD values were measured in three mandibular regions on panoramic images. Independent t-tests and Mann–Whitney U tests were used to compare FD values between groups. The correlations between parameters were evaluated using Pearson and Spearman correlation coefficients. Statistical significance was set at P < 0.05. Results Comparison of the FD values revealed no significant differences between the study and control groups for ROI1 and ROI2 (p > 0.05). However, a statistically significant difference was detected in ROI3 (p < 0.05), with the study group exhibiting lower mean FD values (1.15 ± 0.14) than the control group (1.22 ± 0.08). There was no statistically significant difference in BMI values between the groups (p > 0.05). The frequency of incubation was significantly higher in the study group (50%) than in the control group (6.7%) (p < 0.05). Conclusion Fractal dimension values of the trabecular structure in the dentate region of the mandible were decreased in premature birth and LBW children. Further controlled trials with larger sample sizes are required to validate and expand upon these findings. Clinical trial number Not applicable.